Enhancing Middle School Students’ Conceptual Understanding in Science through the Anticipation Guide Strategy - Yus'iran; Siswanto; Subhan, Muhammad; Amirul, Muhamad Ardi (Universitas Islam Negeri Raden Intan Lampung, 2026)
Persistent deficits in students’ conceptual understanding of science, particularly within Indonesian secondary education, underscore the urgent need for evidence-based instructional interventions that transcend conventional, transmission-oriented pedagogical practice. This study examined whether the implementation of the Anticipation Guide (AG) strategy produces a significantly greater improvement in seventh-grade students’ conceptual understanding of science compared to conventional lecture-based instruction. A quasi-experimental nonequivalent pretest–posttest control group design was adopted. Fifty-two seventh-grade students from SMP Negeri 1 Geyer were assigned to an experimental class (n = 26; AG-based instruction) and a control class (n = 26; conventional lecture-based instruction). Both classes studied the topic of Earth and the Solar System over four 80-minute sessions. Conceptual understanding was assessed using a validated 25-item multiple-choice instrument with a KR-20 reliability coefficient of 0.78. The Shapiro–Wilk test confirmed non-normal score distributions; accordingly, the Wilcoxon signed-rank test was employed for inferential analysis. Normalized Gain (N-Gain) scores were computed to quantify the practical magnitude of pre-to-post improvement. The experimental class demonstrated a statistically significant pre-to-post improvement (Z = −4.489, p < 0.001; N-Gain = 0.436, Moderate category) alongside a pronounced reduction in score variance (34.46 → 10.15). No significant improvement was observed in the control class (Z = −1.003, p = 0.317; N-Gain = 0.012, Low category). The AG strategy, by activating prior knowledge, scaffolding evidence-based evaluation of scientific texts, and reinforcing conceptual consolidation through post-reading reflection, constitutes a significantly more effective instructional approach than conventional direct instruction for promoting conceptual understanding in secondary science education. The study contributes empirical evidence to the limited body of research on reading-based epistemic strategies in under-resourced secondary school contexts.